Understanding the Relationship Between Investors’ Personal Attributes and Investment Perceptions Towards Mutual Fund Investments - Sindhu; Rama Krishna, Y.; Reddy, Adavelli Sagar (Indian Journal of Finance, 2017)
The aim of this paper was to measure the relationship between investors’ personal attributes (educational qualifications, occupation, income, and age) and their investment perceptions (knowledge, information, safety, returns, and decision making). For the purpose of this study, a structured questionnaire was designed and administered to 1000 randomly chosen mutual fund investors in Hyderabad. The usable responses were 522 responses (52.2%). Perceptions of investorsÂ were measured on a Likert scale. The scale reliability scores were satisfactory. Initially, data were analyzed using chi-square test. However, there were near to 40% of the cells that had cell count less than 5. As an alternative to the chi - square test, the hypotheses were tested with the Kruskal-Wallis H Test. The study found a relationship between age of the respondents and safety of investments. No relationship was found between other personal attributes and investment perceptions.